2020
DOI: 10.1007/s40333-020-0078-6
|View full text |Cite
|
Sign up to set email alerts
|

How precipitation and grazing influence the ecological functions of drought-prone grasslands on the northern slopes of the Tianshan Mountains, China?

Abstract: Drought-prone grasslands provide a critical resource for the millions of people who are dependent on livestock for food security. However, this ecosystem is potentially vulnerable to climate change (e.g., precipitation) and human activity (e.g., grazing). Despite this, the influences of precipitation and grazing on ecological functions of drought-prone grasslands in the Tianshan Mountains remain relatively unexplored. Therefore, we conducted a systematic field investigation and a clipping experiment (simulatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Usually, an increase in PD or GDP will impose pressure on the ecosystem [36], which may reduce ecological space, threaten biodiversity, and thereby hinder the supply of ESs [37,38]. Additionally, grazing is the main disturbance to mountainous ecosystems in arid regions, while overgrazing can cause grassland degradation and adversely affect ecosystem functions [39,40]. It is possible to use grazing intensity (GI) to characterize the disturbance level of grazing activities.…”
Section: Selection Of Driving Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Usually, an increase in PD or GDP will impose pressure on the ecosystem [36], which may reduce ecological space, threaten biodiversity, and thereby hinder the supply of ESs [37,38]. Additionally, grazing is the main disturbance to mountainous ecosystems in arid regions, while overgrazing can cause grassland degradation and adversely affect ecosystem functions [39,40]. It is possible to use grazing intensity (GI) to characterize the disturbance level of grazing activities.…”
Section: Selection Of Driving Factorsmentioning
confidence: 99%
“…Large-area grasslands in the Tianshan Mountains are used as pasturelands, so grazing constitutes the primary anthropogenic disturbance to these ecosystems. Moderate grazing can promote plant growth under waterstress conditions [39], whereas overgrazing will lead to the degradation of grasslands and shrubs [22,40], posing a great challenge to the restoration of mountainous ecosystems. At this point, grassland grazing patterns should be improved to maintain a reasonable grazing capacity and reduce the impact of grazing on the ESs provided by mountainous grasslands.…”
Section: Implications and Suggestions For Ecosystem Managementmentioning
confidence: 99%
“…Reliable and accurate precipitation information is essential for water resources and ecosystem management [1][2][3]. However, there are different data sources to obtain precipitation time-series: (i) ground observations, (ii) satellite estimates, and (iii) numerical simulations [4].…”
Section: Introductionmentioning
confidence: 99%
“…However, China's grasslands have been seriously degraded in recent years. Relevant studies have shown that human activities, such as overgrazing, are among the main driving forces leading to grassland degradation [11][12][13][14]. To prevent the continued destruction of the grassland ecological environment by human activities, the Chinese government implemented the policy of subsidies and rewards for grassland ecological protection (PSRGEP) in 2011.…”
Section: Introductionmentioning
confidence: 99%